2000
DOI: 10.1073/pnas.97.7.3678
|View full text |Cite
|
Sign up to set email alerts
|

Protease-activated receptor-2 modulates myocardial ischemia-reperfusion injury in the rat heart

Abstract: Protease-activated receptor-2 (PAR-2) is a member of seven transmembrane domain G protein-coupled receptors activated by proteolytic cleavage whose better known member is the thrombin receptor. The pathophysiological role of PAR-2 remains poorly understood. Because PAR-2 is involved in inflammatory and injury response events, we investigated the role of PAR-2 in experimental myocardial ischemia-reperfusion injury. We show for the first time that PAR-2 activation protects against reperfusion-injury. After PAR-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
98
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 51 publications
7
98
3
Order By: Relevance
“…Although PAR 2 activation seems to be involved in leukocyte migration, inflammation of joints, skin, and kidney, and allergic inflammation of airways, 3 it has also been linked to some protective anti-inflammatory activities via the epithelium and vascular endothelium in the airways, 14 in the mucosal tissues of the gastrointestinal tract, 15 or in response to cardiovascular injury. 42 Conversely, the results from the present study clearly demonstrate that upon infection, PAR 2 plays a proinflammatory role in gingival tissues. Our data demonstrate that in the presence of P. gingivalis, PAR 2 activation leads to a significant increase in inflammatory cell infiltration, which was inhibited by SBTI and significantly reduced in PAR 2 -deficient (PAR 2 Ϫ/Ϫ ) mice.…”
Section: Discussionmentioning
confidence: 35%
“…Although PAR 2 activation seems to be involved in leukocyte migration, inflammation of joints, skin, and kidney, and allergic inflammation of airways, 3 it has also been linked to some protective anti-inflammatory activities via the epithelium and vascular endothelium in the airways, 14 in the mucosal tissues of the gastrointestinal tract, 15 or in response to cardiovascular injury. 42 Conversely, the results from the present study clearly demonstrate that upon infection, PAR 2 plays a proinflammatory role in gingival tissues. Our data demonstrate that in the presence of P. gingivalis, PAR 2 activation leads to a significant increase in inflammatory cell infiltration, which was inhibited by SBTI and significantly reduced in PAR 2 -deficient (PAR 2 Ϫ/Ϫ ) mice.…”
Section: Discussionmentioning
confidence: 35%
“…9) Furthermore, it has been reported that PAR-2-dependent signaling events are involved in heart protection by ischemic-preconditioning. 10) Since the highest levels of tryptase release were observed within 10 min of the onset of ischemia in this study, it is possible that tryptase is released during ischemic preconditioning usually caused by 5 min ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…So far, many reports suggested detrimental effects of PAR-2 activation (11 -17), although PAR-2 activation also showed protective effects in myocardial ischemiareperfusion injury (18), airways (19,20) and cerebral circulation during chronic hypertension (21).…”
mentioning
confidence: 99%